THE INFLUENCE OF FINANCIAL REPORTING SYSTEM, INTERNAL CONTROL AND UNDERSTANDING OF ACCOUNTING INFORMATION SYSTEM ON FINANCIAL PERFORMANCE OF VILLAGE-OWNED ENTERPRISES (BUMK) IN LABANAN MAKMUR VILLAGE - Munawaroh, Siti; Adi Purwanto, Sayugo; Ganie, Djupiansyah (JURNAL EKBIS, 2025)
This study aims to analyze the Understanding of Financial Reporting Systems, Internal Control and Accounting Information Systems on the Financial Performance of Village-Owned Enterprises (BUMK) in Labanan Makmur Village. The sampling technique in this study used a population and collected 34 respondents. The data collection technique in this study used a questionnaire. The data analysis method used the SPSS version 22.0 program as an analysis tool. Based on the results of the analysis, it shows that the Understanding of the accounting system has a positive effect on the financial performance of BUMK at BUMK Labanan Makmur in Berau Regency. The Financial Reporting System has a positive effect on the financial performance of BUMK at BUMK Labanan Makmur in Berau Regency, and the Internal Control System (SPI) has a positive effect on the financial performance of BUMK at BUMK Labanan Makmur in Berau Regency